Axonal regeneration and innervation ratio following supercharged end-to-side nerve transfer - Harnoncourt, Leopold; Schmoll, Martin; Festin, Christopher; Pflaum, Laurenz; Breuss, Markus; Klepetko, Johanna; Dotzauer, Dominik C.; Jaklin, Florian J.; Maierhofer, Udo; Tratnig-Frankl, Philipp; Aszmann, Oskar C. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionPeripheral nerve injuries often result in incomplete recovery, particularly after the occurrence of proximal lesions, owing to the extended reinnervation time as well as consequent reductions in the regeneration supportive factors and muscle recovery potential. In these cases, supercharged end-to-side (SETS) nerve transfers preserve the continuity of the original nerves while facilitating additional axonal support to mitigate muscle atrophy. This approach enhances functional recovery and has been demonstrated to be effective in both preclinical models and clinical settings. In this study, a novel SETS nerve transfer model is presented for the upper extremity of the rat to assess the impacts on muscle function, innervation ratio, and motor neuron regeneration as well as investigate the potential to enhance motor function recovery.MethodsThe surgical interventions include transection and end-to-end repair of the musculocutaneous nerve (MCN) in Group A, transfer of the ulnar nerve (UN) to the side of the MCN in Group B, and a combination of both in Group C. The biceps muscle function was assessed 12 weeks post-surgery using electrical stimulation.ResultsMuscle assessments revealed no significant differences in force between the experimental groups. UN-related muscle reinnervation was observed only in Group C after transfer to a regenerating nerve. Retrograde labeling demonstrated motor neuron regeneration of both the MCN and UN in a distal direction toward the muscle; however, tracer uptake of the UN motor neurons following intramuscular tracer application was detected only in Group C. In contrast, stained pseudounipolar cells in the dorsal root ganglia associated with the UN and MCN revealed afferent muscle innervations in Groups B and C.DiscussionThis novel SETS nerve transfer model enables isolated electrophysiological as well as histological evaluations of all nerve sections to determine the muscle innervation ratio exactly. Our findings indicate that substantial functional efferent muscle innervation by the donor nerve is exclusively observed in a regenerating environment.